2007
DOI: 10.1261/rna.355807
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule disruption stimulates P-body formation

Abstract: Processing bodies (P-bodies) are subcellular ribonucleoprotein (RNP) granules that have been hypothesized to be sites of mRNA degradation, mRNA translational control, and/or mRNA storage. Importantly, P-bodies are conserved from yeast to mammals and contain a common set of evolutionarily conserved protein constituents. P-bodies are dynamic structures and their formation appears to fluctuate in correlation with alterations in mRNA metabolism. Despite these observations, little is understood about how P-body str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 48 publications
6
55
1
Order By: Relevance
“…This clearly indicates that the aggregation into a ribosome free state is not a prerequisite for their degradation. This finding is also consistent with the observation that mRNA degradation can be uncoupled from P-body formation (80)(81)(82)(83). Future experiments investigating the kinetics of mRNA degradation and translation on a transcriptome-wide level will allow a precise quantitative conclusion of which fraction of each transcript is degraded on the ribosome.…”
Section: Discussionsupporting
confidence: 88%
“…This clearly indicates that the aggregation into a ribosome free state is not a prerequisite for their degradation. This finding is also consistent with the observation that mRNA degradation can be uncoupled from P-body formation (80)(81)(82)(83). Future experiments investigating the kinetics of mRNA degradation and translation on a transcriptome-wide level will allow a precise quantitative conclusion of which fraction of each transcript is degraded on the ribosome.…”
Section: Discussionsupporting
confidence: 88%
“…The appearance of P-bodies in the MA3 strains could reflect a general response to stress caused by the mutation because it was shown that exposure of S. cerevisiae cells to various forms of stress, such as glucose deprivation or hypotonic shock, can cause P-body formation (18). P-body formation can also be stimulated by microtubule disruption (20). Indeed, treating wild-type cells with benomyl (a β-tubulin polymerization inhibitor) and/or latruncilin-A (an actin polymerization inhibitor) was found to cause P-body formation (20).…”
Section: Resultsmentioning
confidence: 99%
“…P-body formation can also be stimulated by microtubule disruption (20). Indeed, treating wild-type cells with benomyl (a β-tubulin polymerization inhibitor) and/or latruncilin-A (an actin polymerization inhibitor) was found to cause P-body formation (20). Formation of P-bodies in S. cerevisiae can also be induced by overexpression or deletion of some of their key components (18).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, microtubule depolymerizing drugs prevent assembly of large stress granules 39,40 and germ granules in early zebrafish embryos, 41 whereas P-bodies become larger, and less mobile. 42,43 Specific dynein and kinesin motor proteins also localize in stress granules, and appear to facilitate assembly and disassembly of stress granules, respectively. 40 Dynein proteins also increase P-body assembly under stress.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%